Significado da dor crônica para usuário de um serviço de saúde em Santos, São Paulo. - Silva, Tatiane Barbosa Bispo da (2015)
Pain is considered to be a unique subjective experience with multidimensional aspects not only determined by biological factors. It is given a certain significance according to one´s culture, based on socially accepted patterns that establishes individual and social sanctions, when it comes to tolerating and reacting to pain. Aim: To analyze pain significance to chronic pain patients in a Public Specialty Health Service, in Santos, São Paulo, Brazil. Method: Qualitative Anthropological Research. Techniques: ethnographic observation and in depth interview. Results: Patient-centered care is of the utmost importance in order to provide a thorough evaluation and assistance. There must be a stronger connection between medical knowledge within chronic pain care and the patients` limitations. Chronic pain compromises many dimensions of the individuals` lives. It impacts their financial condition, social life, daily activities, emotional and psychological well-being. Their suffering is intimately related to their life experiences, which can be observed once the interaction between social, cultural and biological factors reflects on the pain outbreak and control. Conclusion: The subjects in the group under study, in all, claim that attending the meetings at the health center gives them support to face the pain by sharing their experiences and supporting one another. They discuss non-conventional strategies and techniques to relieve the pain, and go beyond the indicated treatment, sharing their successful experiences applying alternative therapy, habits, actions and behaviour.